Onomatopoeia in Minions: Banana! Comic and Its Indonesian Version (Translation Approach) - Yunita Widiyantari dan Ni Luh Sintha MW (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Several aims are constructed such as the types of onomatopoeia, the technique of translation,the translation quality and the impact of the technique to the translation quality ofonomatopoeia in children comic entitled “Minions: Banana!” and its translation versionentitled “Minions: Banana!”. Descriptive qualitative method is used. Meanwhile, the data usedin this research consist of two data. The first data is the onomatopoeia words which are foundin comic entitled “Minions: Banana!” both in English and Indonesian version. The second datais questionnaire which are distributed to the three raters. The distributed questionnaires areabout translation technique and translation quality assessment. As the result, there are 63 dataaltogether. There are 2 types of onomatopoeia which are lexical onomatopoeia (22 data or35%), non-lexical onomatopoeia (36 data or 57%), and 5 data or 8% are uncategorized.Futhemore the translation techniques used to translate onomatopoeia are 4 techniques whichare adaptation (8 data or 12,7%), borrowing (32 data or 50,8%), discursive creation (7 data or11,1%), and established equivalent (16 data or 25,4%).Keyword:onomatopoeia, comic, translation technique, quality.